2020
DOI: 10.1016/j.ehb.2019.100815
|View full text |Cite
|
Sign up to set email alerts
|

Growing in the womb: The effect of seismic activity on fetal growth

Abstract: We study how prenatal maternal stress, caused by sustained seismic activity, affects birth outcomes in Chile during the period 2011-2015. A mother-fixed-effect model together with the spatiotemporal variation of earthquakes in Chile allow us to deal with identification issues that have obscured previous estimates. Our findings show that prenatal maternal stress seems to affect fetal growth, because infants born to mothers exposed to earth tremors in early and/or mid gestation are more likely to be large for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In this systematic review, we investigated whether earthquakes increase adverse perinatal outcomes, including 2 607 405 women and 13 studies. [12][13][14][15][38][39][40][41][42][43][44][45][46] Our findings showed that, overall, earthquakes might not increase preterm birth or low birth weight among affected women. Additionally, earthquakes might not reduce the birth of males, gestational age, or birth weight and might not increase stillbirth.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this systematic review, we investigated whether earthquakes increase adverse perinatal outcomes, including 2 607 405 women and 13 studies. [12][13][14][15][38][39][40][41][42][43][44][45][46] Our findings showed that, overall, earthquakes might not increase preterm birth or low birth weight among affected women. Additionally, earthquakes might not reduce the birth of males, gestational age, or birth weight and might not increase stillbirth.…”
Section: Discussionmentioning
confidence: 91%
“…We present the reasons for excluding these studies in Table S3. Consequently, we included 13 studies for analyses 12–15,38–46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that natural disasters and climatic catastrophes may impact health endowment at birth through less direct channels such as prenatal maternal stress (Álvarez-Aranda et al, 2020;Caruso & Miller, 2015;Glynn et al, 2001;Hetherington et al, 2021;Kim et al, 2017;Nandi et al, 2018;Torche, 2011). For instance, Currie & Rossin-Slater (2013) explore the impact of stress-induced by hurricanes on birth outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social insurance also has the potential to influence maternal mental health outcomes and help mothers experience less stressful pregnancies. Since stress has a detrimental influence on birth outcomes, UI payments can be beneficial for infants' health outcomes (Álvarez-Aranda et al, 2020;Bozzoli & Quintana-Domeque, 2014;Noghanibehambari et al, 2020a;Olafsson, 2016).…”
Section: Introductionmentioning
confidence: 99%